Evaluation of oral escherichia coli bacterin and water medication on performance of weaned pigs - Schoneweis, D.A.; Nicholson, R.I.; Fitzner, G.E.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Odd-numbered pigs in new-born litters were vaccinated on d 1 with an oral Escherichia coli bacterin and their performance after weaning was compared with that of nonvaccinated littermates (even numbered pigs). In addition, each group of pigs was allotted to four water medication treatments that were administered from d 2 to d 6 after weaning. No significant interaction between vaccine and water treatment was observed. Vaccinated and non-vaccinated pigs performed similarly throughout the trial for the traits of ADG, ADFI, and F/G, indicating no beneficial effect from vaccination. Water medication after weaning did not affect performance or incidence of scours during the first 14 d. During the next 16 d of the trial, those pigs that had not received water medication grew faster and were 8% more efficient than those that received the Apralan and Genotocin water medications. Overall performance (0 to 30 d) was similar among all water treatments (non-medicated, Apralan, Genotocin, and Neomycin) for the traits of ADG and ADFI. The most efficient pigs were the non-medicated. The incidence of scours was similar for all treatments, except those medicated with Apralan, which had greater incidence.
Keywords: Swine; Weanling pig; E. coli; Water medication